2017
DOI: 10.1038/s41598-017-06752-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazines Enhance Mild Hypothermia-induced Neuroprotection via PI3K/Akt Regulation in Experimental Stroke

Abstract: Physical hypothermia has long been considered a promising neuroprotective treatment of ischemic stroke, but the treatment’s various complications along with the impractical duration and depth of therapy significantly narrow its clinical scope. In the present study, the model of reversible right middle cerebral artery occlusion (MCAO) for 2 h was used. We combined hypothermia (33–35 °C for 1 h) with phenothiazine neuroleptics (chlorpromazine & promethazine) as additive neuroprotectants, with the aim of augmenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…For example, a recent research revealed that MH with bone mesenchymal stem cell transplantation improved the prognosis of rats with cerebral ischemia (19). Combined therapy with phenothiazines and MH also enhanced neuroprotection in ischemic rats through regulating the PI3K/Akt pathway (20). It has also been reported that the Notch inhibitor DAPT combined with MH exerted a synergistic effect on post-stroke seizures (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent research revealed that MH with bone mesenchymal stem cell transplantation improved the prognosis of rats with cerebral ischemia (19). Combined therapy with phenothiazines and MH also enhanced neuroprotection in ischemic rats through regulating the PI3K/Akt pathway (20). It has also been reported that the Notch inhibitor DAPT combined with MH exerted a synergistic effect on post-stroke seizures (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that chlorpromazine protects against neuronal injury by mitigating reactive oxygen species (ROS) accumulation as well as oxidative stress, which results from increased brain metabolism [7]. Promethazine has been observed to reduce mitochondrial permeability during ischemia, mitigating cerebral injury [8,9]. 2…”
Section: Introductionmentioning
confidence: 99%
“…A pivotal mechanism in this context seems to be excitotoxicity, characterized by excessive release and impaired re‐uptake of glutamate, ultimately leading to neurodegeneration and cell death ( Vannucci and Hagberg, 2004 ). A pharmacologic class with the potential to counter these noxious effects are phenothiazines which have been shown to be anti-excitotoxic, anti-apoptotic and anti-oxidative ( Geng et al, 2017 ; An et al, 2017 ; Varga et al, 2017 ; Gonzalez-Munoz et al, 2010 ). The long-standing phenothiazine LMP is currently experiencing a revival due to its favourable risk profile, flexible routes of administration, convenient dosing interval, as well as its potent sedative, analgesic and anaesthetic mechanisms of action ( van der Zwaan et al, 2012 ; Hohl et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also used off-label as an add-on sedative in Pediatric Intensive Care Units, as it appears to have no major side effects ( van der Zwaan et al, 2012 ; Hohl et al, 2013 ; Snoek et al, 2014 ). With regard to brain injury, various phenothiazines proved to be neuroprotective due to their anti-excitotoxic, anti-apoptotic and anti-oxidative properties ( Geng et al, 2017 ; An et al, 2017 ; Varga et al, 2017 ; Gonzalez-Munoz et al, 2010 ). The neuroprotective effect of LMP is a widely under-researched topic, with only two studies showing beneficial effects via inhibition of lipid peroxidase and scavenging reactive oxygen species in vitro ( Hadjimitova et al, 2002 ; Jeding et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%